2011
DOI: 10.1016/j.febslet.2011.11.025
|View full text |Cite
|
Sign up to set email alerts
|

The protein chaperone Ssa1 affects mRNA localization to the mitochondria

Abstract: Edited by Ulrike KutayKeywords: mRNA localization Mitochondria Hsp70 chaperone Ssa1 Tom70 Yeast a b s t r a c t Many nuclear-transcribed mRNAs encoding mitochondrial proteins are localized near the mitochondrial outer membrane. A yet unresolved question is whether protein synthesis is important for transport of these mRNAs to their destination. Herein we present a connection between mRNA localization in yeast and the protein chaperone Ssa1. Ssa1 depletion lowered mRNA association with mitochondria while its ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 43 publications
(52 reference statements)
3
36
0
Order By: Relevance
“…An analysis of cells with reduced levels of this protein revealed a decreased association between mitochondria and certain mRNAs, many of which encode proteins with a high hydrophobic score. 50 These results were consistent with a role for this Hsp70 protein in the folding of hydrophobic domains. Indeed, Ssa1 was shown to interact with RNCs, 77 suggesting that its impact on the localization of mRNAs occurs during their translation.…”
Section: Factors Controlling Localized Translationsupporting
confidence: 79%
See 2 more Smart Citations
“…An analysis of cells with reduced levels of this protein revealed a decreased association between mitochondria and certain mRNAs, many of which encode proteins with a high hydrophobic score. 50 These results were consistent with a role for this Hsp70 protein in the folding of hydrophobic domains. Indeed, Ssa1 was shown to interact with RNCs, 77 suggesting that its impact on the localization of mRNAs occurs during their translation.…”
Section: Factors Controlling Localized Translationsupporting
confidence: 79%
“…Recent studies have revealed the molecular players that are involved in both of these modes (see Section 3). 30,31,50,51 Ribosomes' association with mitochondria can be measured by western analysis of mitochondrial fractions with an antibody that recognizes a ribosomal protein. 31,52 This technique, however, should be interpreted cautiously, as mitochondrial fractions usually contain ER fragments, which also contain ribosomes.…”
Section: Experimental Evidence For Localized Translation Near the Mitmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, translated features such as the AUG, mitochondrial targeting sequence (MTS) or ORF regions were shown to assist in localization 8,11,15 . Hsp70-family protein chaperone and protein receptor on the mitochondria outer membrane were also shown to support mRNA association, further implying that encoded-protein features are important for mRNA localization 16 . This is consistent with a model in which the ribosome-emerging protein serves as recognition element for targeting mRNA-ribosome-protein complex to the mitochondria 17 .…”
Section: Introductionmentioning
confidence: 94%
“…Centrifuge spheroplasts at 3,000 x g for 5 min at 4 °C and discard the supernatant. 16. Wash twice with cold Mannitol Buffer.…”
Section: Mitochondria Purificationmentioning
confidence: 99%